A wolf in sheep's clothing? The NPT and symbolic proliferation. Issue 1 (2nd January 2022) - Noda, Orion
ABSTRACT: I argue that the Treaty on the Non-Proliferation of Nuclear Weapons (NPT) not only fails to address non-quantitative forms of nuclear proliferation, but also acts as a proliferator of the symbolic values of nuclear weapons. Drawing from Semiotics scholarship, I identify two symbolic roles played by the NPT: as a symbol in itself and as a symbolic proliferator. To support my argument, I employ document and critical discourse analyses, examining the text of the treaty as well as statements from selected nuclear weapon states (NWS) and non-nuclear-weapon states (NNWS) at the 2015 NPT Review Conference (RevCon). This article is structured in two sections: Firstly, I put forward an analytical framework focused on symbolism, exploring the symbolic role of nuclear weapons. Secondly, I turn my attention to the NPT, examining its role and success in the past 50 years employing the symbolic analytical framework.